Sebaceous horn over scalp - Bijwe, Pravin Balakrishna; Najan, Deepak Gulab; Hake, Prasad Dasharath (International Journal of Research in Medical Sciences, 2016)
Cutaneous horn is an exophytic keratinized lesion related to sun exposure or burns that most often occurs on the face. Although it is recognized as a slow-growing benign condition, it has also been described as potentially malignant lesion. Only a few cases of cutaneous horn of the scalp have been described in the literature. A 65 year old male came to our hospital with horn like growth over scalp, we did excisional biopsy of the lesion and report came as “sebaceous horn”.on regular follow up, no recurrence has been seen on surgical site.